Double-layer microwave dielectric ceramic material and preparation method thereof

Through the preparation method of double-layer microwave dielectric ceramic materials, the laminated structure design and gradient sintering technology are used to solve the problem of unstable performance of existing ceramic materials in high-temperature and high-frequency environments, and high dielectric constant and temperature stability are achieved , and simplify the preparation process and reduce costs.

CN119118654AActive Publication Date: 2024-12-13GUILIN UNIV OF ELECTRONIC TECH +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411153279.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-13
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

The existing double-layer microwave dielectric ceramic materials have complex manufacturing processes and high production costs, and their performance is unstable in high-temperature and high-frequency environments, which can easily lead to a decrease in microwave signal transmission efficiency and an increase in energy loss.

Method used

Using the preparation method of double-layer microwave dielectric ceramic material, the first and second powders are prepared by preparing titanium dioxide, lanthanum oxide, sodium carbonate, samarium oxide and lithium oxide, and heated at different temperatures to form the main crystal phase, and polyethylene is added. After grinding the alcohol, the sieve is formed to form a laminated sheet of Sm0.5Li0.5TiO3 and La0.5Na0.5TiO3, and sintered at high temperature. The gradient cooling rate is used to control the shrinkage rate to prepare a laminated structure with a flat surface and dense interior.

Benefits of technology

The high dielectric constant, good temperature stability and low energy loss of the material are achieved, the preparation process is simplified, and the cost is reduced. At the same time, the frequency response range is broadened and the overall performance of the material is improved through the stacked structure design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118654A_ABST
    Figure CN119118654A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, in particular to a double-layer microwave dielectric ceramic material and a preparation method thereof.The shrinkage rate is controlled by increasing the pre-sintering temperature, controlling the component lamination pressure and controlling the sintering process, and the laminated structure microwave dielectric ceramic material with the flat surface and the compact interior is prepared. The material not only retains the advantageous performance of each single-layer material, such as high dielectric constant, good temperature stability and the like, but also realizes the complementation and enhancement of the performance through the design of a laminated structure, has the advantages of high dielectric constant, high thermal stability and the like, also has the characteristics of simple preparation process, low cost and the like, and is suitable for industrial production. Therefore, the problems that an existing double-layer microwave dielectric ceramic material is complex in manufacturing process and high in production cost are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a double-layer microwave dielectric ceramic material and a preparation method thereof. Background Art

[0002] In microwave communications and radar systems, the performance requirements for microwave dielectric ceramic materials are becoming increasingly stringent. Although traditional single-layer microwave dielectric ceramic materials have certain dielectric constants, quality factors and temperature coefficients, their performance often cannot meet actual needs in certain special application scenarios, such as high temperature, high frequency or high power environments. In particular, the performance limitations of single-layer materials may lead to reduced microwave signal transmission efficiency, increased energy loss, and may even cause system failure. As a result, the performance is improved by mixing ceramic powders of different systems to form solid solutions. Ceramic solid solutions do have unique advantages in improving the performance of microwave dielectric ceramic materials. For example, key performance parameters such as dielectric constants, quality factors and temperature coefficients can be optimized by adjusting the proportion of different components in the solid solution.

[0003] However, ceramic solid solutions also have some limitations. First, the preparation process of ceramic solid solutions is relatively complex, and it is necessary to precisely control the mixing ratio and sintering conditions of different ceramic powders. This not only increases the production cost, but also may lead to instability in product performance due to slight differences in the preparation process. Secondly, when different powders are mixed to form a ceramic solid solution, different chemical substances have their specific solubility limits in the solid solution. If these limits are exceeded, phase separation or other non-ideal structures may be formed, affecting the performance and stability of the material. In addition, the lattices of different compounds are often not completely matched, especially when the solid solution composition is quite different. This may lead to lattice distortion, stress concentration or the formation of grain boundaries, affecting the mechanical properties and durability of the material, etc. In addition, although the dielectric properties of ceramic solid solutions can be optimized by adjusting the component ratio, their performance may still be limited under certain extreme conditions, such as ultra-high temperature or ultra-high frequency environments. This is because different components in the solid solution may produce phase changes or changes in conductivity at high temperature or high frequency, thereby affecting its overall performance.

[0004] The traditional random distribution process inevitably leads to different defects due to the possible incompatibility between crystal structure, ionic charge, and ionic radius. Summary of the invention

[0005] The object of the present invention is to provide a double-layer microwave dielectric ceramic material and a preparation method thereof, aiming to solve the problem that the existing double-layer microwave dielectric ceramic material has a complex manufacturing process and a high production cost.

[0006] To achieve the above object, in a first aspect, the present invention provides a double-layer microwave dielectric ceramic material, comprising the following steps:

[0007] Prepare titanium dioxide, lanthanum oxide, sodium carbonate, samarium oxide and lithium oxide, and dry them in an oven;

[0008] preparing a first powder and a second powder based on the titanium dioxide, the lanthanum oxide, the sodium carbonate, the samarium oxide and the lithium oxide;

[0009] Weigh 40 g of the first powder and heat it at 1050° C. for 2 h to obtain a first main crystalline phase; weigh 40 g of the second powder and heat it at 950° C. for 2 h to obtain a second main crystalline phase;

[0010] Add 8 wt % polyvinyl alcohol to the first main crystalline phase and the second main crystalline phase respectively, grind for 1 hour, sieve, and dry in an oven at 100° C. for 6 hours to obtain Sm 0.5 Li 0.5 TiO3 and La 0.5 Na 0.5 TiO3;

[0011] Weigh 1gSm 0.5 Li 0.5 TiO3 is put into the mold and pressed into shape, then 1g La is added 0.5 Na 0.5 TiO3 is pressed for 4-5 minutes to obtain a laminated sheet;

[0012] The laminated sheet is sintered at 1250° C.-1300° C. for 4 hours, cooled to 800° C. at a cooling rate of 50° C. / h, and then naturally cooled to room temperature to obtain a laminated ceramic sheet.

[0013] Wherein, in “preparing a first powder and a second powder based on the titanium dioxide, the lanthanum oxide, the sodium carbonate, the samarium oxide and the lithium oxide”, it includes:

[0014] Mixing preset weights of the lanthanum oxide, sodium carbonate and titanium dioxide to obtain a first mixture;

[0015] Mixing preset weights of the samarium oxide, the lithium oxide, and the titanium dioxide to obtain a second mixed material;

[0016] The first mixed material and the second mixed material are respectively placed in a ball milling jar, and anhydrous ethanol is added thereto for ball milling to obtain a first slurry and a second slurry;

[0017] The first slurry and the second slurry are respectively poured into beakers, and the alcohol is dried at a preset temperature to obtain a first powder and a second powder, and the first powder and the second powder are sieved.

[0018] Among them, in “mixing preset weights of the lanthanum oxide, sodium carbonate and titanium dioxide to obtain a first mixture”, the preset weight of the lanthanum oxide is 17.2852 g (±0.0005 g), the preset weight of the sodium carbonate is 5.6293 g (±0.0005 g), and the preset weight of the titanium dioxide is 17.1056 g (±0.0005 g).

[0019] Among them, in “mixing preset weights of the samarium oxide, the lithium oxide and the titanium dioxide to obtain a second mixture”, the preset weight of the samarium oxide is 19.8968 g (±0.0005 g), the preset weight of the lithium oxide is 1.7304 g (±0.0005 g), and the preset weight of the titanium dioxide is 18.3966 g (±0.0005 g).

[0020] Among them, in “weigh 40g of the first powder and heat it at 1050°C for 2h to obtain the first main crystal phase, weigh 40g of the second powder and heat it at 950°C for 2h to obtain the second main crystal phase”, the heating temperature rise rate of the first powder and the second powder is 2°C / min.

[0021] Among them, in "the laminated sheet is sintered at 1250℃-1300℃ for 4h, the laminated sheet is cooled to 800℃ at a cooling rate of 50℃ / h, and then naturally cooled to room temperature to obtain a laminated ceramic sheet", when the laminated sheet is heated to 500℃, it is kept warm for 4h to discharge the binder, and the heating rate is 2℃ / min for a heating rate of 20℃-550℃, and 5℃ / min for a heating rate of 55℃-1250℃.

[0022] In a second aspect, a double-layer microwave dielectric ceramic material is prepared by the method for preparing the double-layer microwave dielectric ceramic material according to the first aspect.

[0023] Including Sm 0.5 Li 0.5 TiO3 / La 0.5 Na 0.5 TiO3 laminated sheets.

[0024] The invention discloses a method for preparing a double-layer microwave dielectric ceramic material, comprising the following steps: preparing titanium dioxide, lanthanum oxide, sodium carbonate, samarium oxide and lithium oxide, and drying them in an oven; preparing a first powder and a second powder based on the titanium dioxide, lanthanum oxide, sodium carbonate, samarium oxide and lithium oxide; weighing 40g of the first powder and heating it at 1050°C for 2h to obtain a first main crystal phase, and weighing 40g of the second powder and heating it at 950°C for 2h to obtain a second main crystal phase; adding polyvinyl alcohol with a mass fraction of 8wt% to the first main crystal phase and the second main crystal phase, grinding for 1h, sieving, and adding them to a 100°C oven for drying for 6h to obtain Sm0.5 Li 0.5 TiO3 and La 0.5 Na 0.5 TiO3; weigh 1gSm 0.5 Li 0.5 TiO3 is put into the mold and pressed into shape, then 1g La is added 0.5 Na 0.5 TiO3 is pressed for 4-5 minutes to obtain a laminated sheet; the laminated sheet is sintered at 1250-1300°C for 4 hours, and the laminated sheet is cooled to 800°C at a cooling rate of 50°C / h, and then naturally cooled to room temperature to obtain a laminated ceramic sheet. The present invention controls the shrinkage rate by increasing the pre-firing temperature, controlling the component lamination pressure and controlling the sintering process, and prepares a laminated structure microwave dielectric ceramic material with a smooth surface and dense interior. The material not only retains the advantages of each single-layer material, such as high dielectric constant and good temperature stability, but also achieves complementary and enhanced performance through the design of the laminated structure. The material not only has the advantages of high dielectric constant and high thermal stability, but also has the characteristics of simple preparation process and low cost, thereby solving the problem of complex manufacturing process and high production cost of existing double-layer microwave dielectric ceramic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 The present invention provides a flow chart of a method for preparing a double-layer microwave dielectric ceramic material.

[0027] Figure 2 This is a flowchart of step S2.

[0028] Figure 3 It's La 0.5 Na 0.5 TiO3-Sm 0.5 Li 0.5 Schematic diagram of TiO3 microwave ceramic laminate.

[0029] Figure 4 It is a longitudinal scanning electron microscope image of SLT-LNT ceramics. DETAILED DESCRIPTION

[0030] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0031] See also Figures 1 to 4 In a first aspect, the present invention provides a double-layer microwave dielectric ceramic material, comprising the following steps:

[0032] S1 prepares titanium dioxide, lanthanum oxide, sodium carbonate, samarium oxide and lithium oxide, and puts them into an oven for drying;

[0033] Specifically, the required raw materials such as titanium dioxide (purity 99.0%), lanthanum oxide (purity 99.9%), sodium carbonate (99.8%), samarium oxide (purity 99.9%), and lithium oxide (purity 99.99%) are placed in an oven at 100°C and dried for 24 hours.

[0034] S2 prepares a first powder and a second powder based on the titanium dioxide, the lanthanum oxide, the sodium carbonate, the samarium oxide and the lithium oxide;

[0035] S21: mixing the lanthanum oxide, sodium carbonate and titanium dioxide with preset weights to obtain a first mixed material;

[0036] The preset weight of the lanthanum oxide is 17.2852 g (± 0.0005 g), the preset weight of the sodium carbonate is 5.6293 g (± 0.0005 g), and the preset weight of the titanium dioxide is 17.1056 g (± 0.0005 g).

[0037] Specifically, according to La 0.5 Na 0.5 Chemical formula of TiO3: Mix 17.2852 g (± 0.0005 g) of lanthanum oxide, 5.6293 g (± 0.0005 g) of sodium carbonate, and 17.1056 g (± 0.0005 g) of titanium dioxide powder.

[0038] S22: mixing the samarium oxide, the lithium oxide and the titanium dioxide with a preset weight to obtain a second mixed material;

[0039] The preset weight of the samarium oxide is 19.8968 g (±0.0005 g), the preset weight of the lithium oxide is 1.7304 g (±0.0005 g), and the preset weight of the titanium dioxide is 18.3966 g (±0.0005 g).

[0040] Specifically, according to Sm 0.5 Li 0.5Chemical formula of TiO3: Mix 19.8968g (±0.0005g) of samarium oxide, 1.7304g (±0.0005g) of lithium oxide, and 18.3966g (±0.0005g) of titanium dioxide powder.

[0041] S23: putting the first mixed material and the second mixed material into a ball mill respectively, and adding anhydrous ethanol to each of them for ball milling to obtain a first slurry and a second slurry;

[0042] Specifically, the obtained mixed powders are respectively loaded into a ball mill, anhydrous ethanol is added as a ball milling medium, and the sodium lanthanum titanate and lithium samarium titanate-based ceramic powders, zirconium oxide balls and anhydrous ethanol are respectively mixed in a mass ratio of 1:2:1 to obtain a mixed product, and then ball milling is performed for 24 hours to fully mix them. After the ball milling is completed, the first slurry and the second slurry are obtained.

[0043] S24: Pour the first slurry and the second slurry into beakers respectively, dry the alcohol at a preset temperature to obtain a first powder and a second powder, and sieve the first powder and the second powder.

[0044] Specifically, the slurries were poured into beakers respectively, and placed in an oven at 100° C. to 120° C. until the alcohol was completely evaporated. The powders were ground for 1 hour respectively and then sieved with a 100-mesh sieve.

[0045] S3: weighing 40 g of the first powder and heating it at 1050° C. for 2 h to obtain a first main crystalline phase; weighing 40 g of the second powder and heating it at 950° C. for 2 h to obtain a second main crystalline phase;

[0046] The heating rate of the first powder and the second powder is 2° C. / min.

[0047] Specifically, in order to make the prepared laminate have good matching in the diameter direction, La 0.5 Na 0.5 TiO3 (40 g), Sm 0.5 Li 0.5 TiO3 (40 g) raw powder was pre-sintered at 1050°C and 950°C for 2 h to form the main crystalline phase (heating rate 2°C / min).

[0048] S4: Add 8 wt% polyvinyl alcohol to the first main crystalline phase and the second main crystalline phase, grind for 1 hour, sieve, and dry in an oven at 100° C. for 6 hours to obtain Sm 0.5 Li 0.5 TiO3 and La 0.5 Na 0.5 TiO3;

[0049] Specifically, the sintered La0.5 Na 0.5 TiO3、Sm 0.5 Li 0.5 Add 50-60 drops of 8wt% polyvinyl alcohol to the TiO3 powder and grind it for 1 hour to fully mix the powder and the binder. After grinding, pass the resulting powder through a 100-mesh sieve and then dry it in an oven at 100°C for 6 hours.

[0050] S5 weighs 1gSm 0.5 Li 0.5 TiO3 is put into the mold and pressed into shape, then 1g La is added 0.5 Na 0.5 TiO3 is pressed for 4-5 minutes to obtain a laminated sheet;

[0051] Specifically, weigh 1gSm 0.5 Li 0.5 TiO3, poured into the mold, gently pressed the head to make it preformed, and then added 1gLa 0.5 Na 0.5 TiO3 is pressed at a pressure of 4MPa for 4 to 5 minutes to obtain a disc with a diameter of about 11mm and a height of about 7mm. The tableting process is carried out using an open-petal mold, which consists of a pressure head, a base, a mold cavity, an outer ring, and a pressure-bearing gasket. The mold cavity is placed on the base and fixed with an outer ring before adding powder to the mold cavity. After many experiments, it is finally selected to maintain the pressure at 4MPa for 4 to 5 minutes to ensure the quality of the tableting. The surface of the resulting green sheet is smooth and crack-free. When taking the sheet, it is only necessary to separate the mold cavity from the outer ring, eliminating the demoulding process and avoiding the damage of the sheet caused by the extrusion of the sheet during the demoulding process.

[0052] S6: sintering the laminated sheet at 1250° C.-1300° C. for 4 hours, cooling the laminated sheet to 800° C. at a cooling rate of 50° C. / h, and then naturally cooling the laminated sheet to room temperature to obtain a laminated ceramic sheet.

[0053] When the laminate is heated to 500°C, it is kept warm for 4 hours to discharge the binder. The heating rate is 2°C / min for 20°C-550°C and 5°C / min for 55°C-1250°C.

[0054] Specifically, the obtained Sm 0.5 Li 0.5 TiO3 / La 0.5 Na 0.5After the TiO3 laminated sheet was sintered at 1250℃~1300℃ for 4h, the cooling rate was controlled at 50℃ / h. After cooling to 800℃, it was naturally cooled to room temperature. The low cooling rate in the high temperature zone can effectively prevent the bending and delamination of heterogeneous materials. During this period, the binder was discharged by keeping at 550℃ for 4h. The heating rate from 20℃ to 550℃ was 2℃ / min, and the heating rate from 55℃ to 1250℃ was 5℃ / min. Finally, a laminated ceramic sheet with a diameter of about 10mm and a height of 5mm was obtained. Compared with the laminated ceramic sheet prepared by the traditional cylindrical demolding mold, the obtained laminated sheet has good effect, and the surface and the middle interface are intact without cracks.

[0055] Table 1 EDS data of selected areas in SEM images

[0056] Spectrum La(at%) Na(at%) Sm(at%) Ti(at%) O(at%) Spectrum Figure 4 1.52 5.42 6.23 15.57 71.26 Spectrum 5 4.53 5.08 4.65 17.46 68.28 Spectrum 7 1.59 4.78 7.14 16.40 70.09 Spectrum 9 2.86 4.77 6.45 17.48 68.44

[0057] The upper side of the SEM image belongs to Sm 0.5 Li 0.5 TiO3 layer, while the lower side belongs to La 0.5 Na 0.5 TiO3 layer. At the same time, La 3+ 、Na + and Sm 2+ , Li + Diffusion within a certain range creates a dense middle layer, which acts as glue to bond the layers together and prevents them from aging.

[0058] In a second aspect, a double-layer microwave dielectric ceramic material is prepared by the method for preparing the double-layer microwave dielectric ceramic material according to the first aspect.

[0059] Including Sm 0.5 Li 0.5 TiO3 / La 0.5 Na 0.5 TiO3 laminated sheets.

[0060] Beneficial effects:

[0061] 1. The design of the laminated structure enables the material to have a wider frequency response range within the microwave frequency band, and can show higher signal transmission efficiency and lower energy loss in microwave communication and radar systems. Because of the laminated structure, ceramic layers with different properties can form a good interface bond, thereby avoiding reflection and scattering of signals during transmission and improving signal transmission efficiency. At the same time, the laminated structure can also effectively reduce the energy loss inside the material and improve the overall performance of the system. 0.5 Na 0.5 TiO3、Sm 0.5 L i 0.5There are differences in the performance of the two materials TiO3 in the microwave frequency band. Combining them into a stacked structure can effectively broaden the frequency response range of the material, making it adaptable to a wider range of application scenarios.

[0062] Second, the laminated structure also improves the dielectric properties and thermal stability of the material. 0.5 L i 0.5 The dielectric constant of TiO3 is about 52, while pure La 0.5 Na 0.5 The dielectric constant of TiO3 is about 122. After testing the dielectric properties of the prepared laminated microwave ceramic, its dielectric constant is about 92.495. In microwave communication and radar systems, the temperature stability of the material is a very important indicator. Through the design of the laminated structure, microwave ceramics can maintain stable performance under different temperature conditions, thereby ensuring the reliability of the system in various environments. This temperature stability is of great significance for improving the long-term operation stability of the system and reducing maintenance costs. 0.5 Na 0.5 The resonant frequency temperature coefficient of TiO3 is generally around +480ppm / ℃, while Sm 0.5 L i 0.5 The resonant frequency temperature coefficient of TiO3 is generally around -260ppm / ℃. The temperature coefficient of the prepared laminate was measured to be approximately +200ppm / ℃, which also shows that the design of the laminate structure achieves complementary and enhanced performance.

[0063] 3. When the proportion of raw materials in the laminated ceramic sheet is changed, its performance also changes accordingly. When 1.2gSm 0.5 L i 0.5 TiO3 and 0.8 g La 0.5 Na 0.5 When TiO3 is used to prepare multilayer ceramics, its dielectric constant is reduced to 78.004. 0.5 L i 0.5 TiO3 and 0.6 g La 0.5 Na 0.5 When TiO3 is used to prepare multilayer ceramics, its dielectric constant is reduced to 69.323, while 0.8g Sm 0.5 L i 0.5 TiO3 and w1.2g La 0.5 Na 0.5 When TiO3 is used to prepare multilayer ceramics, its dielectric constant is increased to 101.293. 0.5 L i 0.5 TiO3 and 1.4 g La 0.5 Na0.5 When TiO3 is used to prepare multilayer ceramics, its dielectric constant is increased to 107.672. This shows that we can adjust the proportion of each layer according to the needs when preparing multilayer ceramics to obtain better performance. By reasonably selecting the pre-sintering temperature and co-sintering temperature of the materials, we have successfully achieved good matching of the multilayer sheets in the diameter direction (such as Figure 3 ), avoiding the problems of cracking and performance degradation caused by mismatched shrinkage coefficients. At the same time, each layer of material in the laminated structure can independently exert its excellent performance, thereby improving the performance of the entire material, and the preparation process is simpler than that of ceramic solid solution, eliminating the process of mixing and ball milling different ceramic powders, and reducing the time required for preparation. Finally, the preparation method of laminated microwave dielectric ceramic materials is simple, easy and low-cost. By adopting optimization measures such as gradient heating and increasing the insulation time, it can be ensured that the thermal stress distribution between the layers of the laminated ceramic during the sintering process is more uniform, reducing the occurrence of problems such as cracking and deformation. At the same time, the preparation method is also highly controllable and repeatable, and can easily prepare laminated microwave dielectric ceramic materials with different properties and structures.

[0064] The above disclosure is only a preferred embodiment of a double-layer microwave dielectric ceramic material and a preparation method thereof of the present invention. Of course, this cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiments and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A method for preparing a double-layer microwave dielectric ceramic material, characterized in that: The following steps are involved: Prepare titanium dioxide, lanthanum oxide, sodium carbonate, samarium oxide and lithium oxide, and dry them in an oven; preparing a first powder and a second powder based on the titanium dioxide, the lanthanum oxide, the sodium carbonate, the samarium oxide and the lithium oxide; Weigh 40 g of the first powder and heat it at 1050° C. for 2 h to obtain a first main crystalline phase; weigh 40 g of the second powder and heat it at 950° C. for 2 h to obtain a second main crystalline phase; Add 8 wt % polyvinyl alcohol to the first main crystalline phase and the second main crystalline phase respectively, grind for 1 hour, sieve, and dry in an oven at 100° C. for 6 hours to obtain Sm 0.5 Li 0.5 TiO3 and La 0.5 Na 0.5 TiO3; Weigh 1gSm 0.5 Li 0.5 TiO3 is put into the mold and pressed into shape, then 1g La is added 0.5 Na 0.5 TiO3 is pressed for 4-5 minutes to obtain a laminated sheet; The laminated sheet is sintered at 1250° C.-1300° C. for 4 hours, cooled to 800° C. at a cooling rate of 50° C. / h, and then naturally cooled to room temperature to obtain a laminated ceramic sheet.

2. The method for preparing a double-layer microwave dielectric ceramic material according to claim 1, characterized in that: In “preparing a first powder and a second powder based on the titanium dioxide, the lanthanum oxide, the sodium carbonate, the samarium oxide and the lithium oxide”, comprising: Mixing preset weights of the lanthanum oxide, sodium carbonate and titanium dioxide to obtain a first mixture; Mixing preset weights of the samarium oxide, the lithium oxide, and the titanium dioxide to obtain a second mixed material; The first mixed material and the second mixed material are respectively placed in a ball milling jar, and anhydrous ethanol is added thereto for ball milling to obtain a first slurry and a second slurry; The first slurry and the second slurry are respectively poured into beakers, and the alcohol is dried at a preset temperature to obtain a first powder and a second powder, and the first powder and the second powder are sieved.

3. The method for preparing a double-layer microwave dielectric ceramic material according to claim 2, characterized in that: In "mixing preset weights of the lanthanum oxide, sodium carbonate and titanium dioxide to obtain a first mixture", the preset weight of the lanthanum oxide is 17.2852 g (±0.0005 g), the preset weight of the sodium carbonate is 5.6293 g (±0.0005 g), and the preset weight of the titanium dioxide is 17.1056 g (±0.0005 g).

4. The method for preparing a double-layer microwave dielectric ceramic material according to claim 2, characterized in that: In "mixing preset weights of the samarium oxide, the lithium oxide and the titanium dioxide to obtain a second mixture", the preset weight of the samarium oxide is 19.8968 g (±0.0005 g), the preset weight of the lithium oxide is 1.7304 g (±0.0005 g), and the preset weight of the titanium dioxide is 18.3966 g (±0.0005 g).

5. The method for preparing a double-layer microwave dielectric ceramic material according to claim 1, characterized in that: In "weighing 40 g of the first powder and heating it at 1050°C for 2 hours to obtain a first main crystalline phase, weighing 40 g of the second powder and heating it at 950°C for 2 hours to obtain a second main crystalline phase", the heating temperature rise rate of the first powder and the second powder is 2°C / min.

6. The method for preparing a double-layer microwave dielectric ceramic material according to claim 1, characterized in that: In the step of "sintering the laminate at 1250°C-1300°C for 4h, cooling the laminate to 800°C at a cooling rate of 50°C / h, and naturally cooling the laminate to room temperature to obtain a laminated ceramic sheet", when the laminate is heated to 500°C, it is kept warm for 4h to discharge the binder, and the heating rate is 2°C / min for a heating rate of 20°C-550°C and 5°C / min for a heating rate of 55°C-1250°C.

7. A double-layer microwave dielectric ceramic material, prepared by the method for preparing a double-layer microwave dielectric ceramic material according to any one of claims 1 to 6, characterized in that: Including Sm 0.5 Li 0.5 TiO3 / La 0.5 Na 0.5 TiO3 laminated sheets.

Citation Information

Patent Citations

  • High-permittivity microwave dielectric ceramics capable of being sintered at medium-low temperature and preparation method thereof

    CN103274684A

  • Microwave dielectric ceramic material and preparation method thereof

    CN103936409A

  • Monolithic ceramic capacitor

    CN1173725A

  • Method for producing laminated dielectric

    CN1819980A

  • Dielectric substance and laminated ceramic electronic component containing the same

    JP2021191721A